ANALYSIS OF OBSTACLES IN IMPLEMENTING FINANCIAL ACCOUNTING STANDARDS FOR MICRO SMALL AND MEDIUM ENTITIES IN MSMEs IN KUPANG CITY - Lamaya, Fauziah (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The purpose of this study was to find out the obstacles in implementing SAK EMKM for MSMEs in Kupang City. The research method used is qualitative. Data analysis was performed using Nvivo 12 Plus with the process of coding analysis, matrix coding queries, word frequency queries, analytical maps, framework matrices, and drawing conclusions as the last step. The results showed that the obstacles in implementing SAK EMKM for MSMEs in Kupang City were mostly caused by external factors, namely unclear socialization. This is due to the socialization methods carried out by socialization organizers who are less effective and the lack of ongoing assistance also causes MSME actors to not understand the material presented.